2020
DOI: 10.1002/bsl.2474
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of two violence risk assessment tools in a psychiatric prison hospital population

Abstract: The risk of violent behavior is known to be higher for patients who suffer from a severe mental disorder. However, specific prediction tools for clinical work in prison psychiatry are lacking. In this single-center study, two violence risk assessment tools (Forensic Psychiatry and Violence Tool, "FoVOx," and Mental Illness and Violence Tool, "OxMIV") were applied to a prison hospital population with a primary psychotic or bipolar disorder and subsequently compared. The required information on all items of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Web-based diagnostics have been widely utilized by researchers to detect risks and facilitate decision making in a range of contexts, including the prediction of chronic disease [33,34], violent behavior [35], self-care [36], and preventive medicine [37]. Therefore, the objective of our work is to design and implement a web-based cancer screening tool that will aid the medical team in making screening decisions.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Web-based diagnostics have been widely utilized by researchers to detect risks and facilitate decision making in a range of contexts, including the prediction of chronic disease [33,34], violent behavior [35], self-care [36], and preventive medicine [37]. Therefore, the objective of our work is to design and implement a web-based cancer screening tool that will aid the medical team in making screening decisions.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Previous studies have shown the effectiveness and usefulness of web-based risk assessments in identifying risks and assisting the decision-making for pediatric readmission prediction [34], preventive medicine [35], violent behavior prediction [36], and trauma therapy [37]. Thus, in this section, we aim to design and develop web-based self-care prediction application (web-app) to provide decision tools for therapist in diagnosing children with disabilities.…”
Section: Practical Application Of the Proposed Self-care Prediction Mmentioning
confidence: 99%
“…As suggested by Demšar [33], a statistical significance test can be utilized to prove the significance of the proposed model as compared to other classification models. Furthermore, previous studies have also reported the effectiveness and usefulness of the practical application of prediction model to identify risks and assist the decision-making for pediatric readmission prediction [34], preventive medicine [35], violent behavior prediction [36], and trauma therapy [37].…”
Section: Introductionmentioning
confidence: 99%
“…For years, forensic psychology research has been concerned with demonstrating the reliability and predictive validity of violence risk assessment tools [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Currently, there are more than 200 violence risk assessment tools with a wide range of applications and varying levels of accuracy [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%